Pengaruh Gaji terhadap Kinerja Guru Honorer di Persekolahan Yayasan Pendidikan Katolik Keuskupan Manado Perwakilan Tomohon - Fecky Evendy Singal; Jearne Felix Imbang; Daniel Dominggus Kandunmas (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
In improving teacher performance to be better and optimal, to create quality and useful human resources for the future of the nation. One of the factors supporting the improvement of teacher performance is salary. Salary is a reward for services or work. But at this time the salary received by honorary teachers is still very less. This study aims to determine the effect of salary on the performance of honorary teachers. This research was conducted in May 2023 at the Tomohon YPK-KM school. The respondents in this study were honorary teachers who were at the YPK-KM school representing Tomohon. The research method used is quantitative. The sampling technique uses the Slovin technique. The sample studied amounted to 126 teachers. The research instrument used was a questionnaire (questionnaire) with alternative answers Strongly Agree (4), Agree (3), Disagree (2), and Disagree (1). This quantitative research uses simple linear regression analysis. The results of the study show that there is an effect of salary on the performance of honorary teachers. This is evidenced by the results of the calculated F value of 14.197 with a significance level of 0.000 <0.005, and a correlation or relationship of 0.321 and a coefficient of determination of 10.3%. Thus there is a very low and significant effect of salary on the performance of honorary teachers. Salary can be said to influence and contribute to improving the performance of honorary teachers at YPK-KM schools representing Tomohon.